Dietary yeast extract prevents alcoholic liver disease in mice via correcting gut dysbiosis and improving intestinal barrier function - Hao Han; Lei Tian; Yajing Dong; Yanyang Han; Xiaoman Wang; Qian Cheng; Haibo Zhang; Yan Zhang (Food Science and Human Wellness)
Alcoholic liver disease (ALD) is one of the major global public health problems. Yeast extract (YE), a product prepared from yeast, has been proven to have antioxidant and anti-inflammatory properties. However, the potential role of YE in the prevention of ALD remains unclear. The present study aimed to investigate the protective effects of YE on ALD and explore the underlying mechanism based on gut microbiota. The result showed that YE supplementation significantly ameliorated chronic alcohol exposure-induced liver injury in mice. In addition, YE counteracted alcohol-induced gut dysbiosis, intestinal barrier dysfunction, lipopolysaccharide (LPS) leakage-induced inflammatory response in the liver. Moreover, microbiota depletion by a broad-spectrum antibiotic was sufficient to block the protective effect of YE on ALD, indicating the contribution of gut dysbiosis modulation to the hepatoprotective role of YE. Furthermore, we demonstrated the causal relationship between gut microbiota and hepatoprotective effects of YE with the fecal microbiota transplantation (FMT) experiment. Compared with the ALD-FMT mice, gut dysbiosis, intestinal barrier dysfunction, LPS/TLR4 signaling pathway activation, and liver inflammatory response were significantly improved in the YE-FMT mice. Together, our findings highlight that dietary YE protects against ALD through gut dysbiosis correction.